Antropogenic-hearth illness of habitants of large city - V. B. Antonov (Журнал инфектологии)
In the conditions of large city the anthropogenic hearths of sporadic and mass diseases, related to influence of ecosystem of buildings of dwelling and production activity of man are formed. Concept about anthropogenic-hearth illnesses can serve as the effective instrument of their prophylaxis.